First in vivo visualization of the human subarachnoid space and brain cortex via optical coherence tomography. (April 2019) - Hartmann, Karl; Stein, Klaus-Peter; Neyazi, Belal; Sandalcioglu, Ibrahim Erol
The present work explores optical coherence tomography (OCT) as a suitable in vivo neuroimaging modality of the subarachnoid space (SAS). Patients ( n = 26) with frontolateral craniotomy were recruited. The temporal and frontal arachnoid mater and adjacent anatomical structures were scanned using microscope-integrated three-dimensional OCT, (iOCT). Analysis revealed a detailed depiction of the SAS (76.9%) with delineation of the internal microanatomical structures such as the arachnoid barrier cell membrane (ABCM; 96.2%), trabecular system (50.2%), internal blood vessels (96.2%), pia mater (26.9%) and the brain cortex (96.2%). Orthogonal distance measuring was possible. The SAS showed a mean depth of 570 µm frontotemporal. The ABCM showed a mean depth of 74 µm frontotemporal. These results indicate that OCT provides a dynamic, non-invasive tool for real-time imaging of the SAS and adjacent anatomical structures at micrometer spatial resolution. Further studies are necessary to evaluate the value of OCT during microsurgical procedures.